Gonococcal and Non-Gonococcal Urethritis in a Global Travel Hub: A Retrospective Analysis of Syndromic Management, Suboptimal Cefixime Monotherapy, and the Public Health Crisis of Patient Retention in Bali, Indonesia - Andrew Wicaksono; I Gusti Ayu Agung Elis Indira; Ni Made Dwi Puspawati; Aditya Permana; Nyoman Suryawati (HM Publisher, 2025)
Background: The inexorable rise of antimicrobial resistance (AMR) in Neisseria gonorrhoeae represents a formidable threat to global public health, jeopardizing the efficacy of last-line treatments for gonococcal urethritis (GO). Southeast Asia is a recognized epicenter for the emergence and dissemination of AMR, yet granular surveillance data from many high-risk localities remain critically sparse. This study aimed to provide a comprehensive characterization of the clinical epidemiology, frontline management practices, and patient outcomes of male urethritis at a tertiary referral center in Bali, Indonesia—a major international crossroads for tourism and migration. Methods: A retrospective, cross-sectional analysis was conducted on the medical records of male patients diagnosed with urethritis at the Dermatology and Venereology Polyclinic of Ngoerah Hospital between January 1st, 2021, and December 31st, 2024. A rigorous screening process of 215 initial records was undertaken to identify eligible cases. Data on sociodemographics, behavioral risk factors, clinical presentation, syndromic diagnosis, prescribed pharmacotherapy, and follow-up adherence were systematically extracted and analyzed using descriptive and comparative statistics. Results: From the initial cohort, 58 male patients met the final inclusion criteria. The cohort was predominantly diagnosed with GO (n=39, 67.2%) over non-gonococcal urethritis (NGO) (n=19, 32.8%). Patients were primarily of productive age (25–44 years, 58.6%) and reported high-risk behaviors, including multiple sexual partners (65.5%). A critical deviation from international treatment guidelines was identified: 97.4% (38/39) of GO patients received oral cefixime 400 mg monotherapy, a regimen no longer recommended for first-line use due to AMR concerns. Furthermore, a profound fracture in the care cascade was evident, with an overall loss-to-follow-up rate of 58.6% (34/58). This failure was most pronounced in the GO cohort, where 76.9% (30/39) of patients did not return for scheduled follow-up, a rate significantly higher than the 21.1% (4/19) observed in the NGO cohort (p<0.001). Conclusion: The clinical management of gonorrhoea at this major Indonesian referral center is defined by two systemic failures: the routine prescription of a suboptimal antimicrobial monotherapy and a near-total collapse of patient follow-up. This combination, situated in a high-transience international hub, creates an unmonitored, high-risk environment for the selection, amplification, and global dissemination of antimicrobial-resistant N. gonorrhoeae. These findings signal an urgent imperative to align local therapeutic protocols with evidence-based global standards and to implement robust, innovative strategies to ensure patient retention and verify the cure.